Alpha-Tocopherol, a Powerful Molecule, Leads to the Formation of Oxylipins in Polyunsaturated Oils Differently to the Temperature Increase: A Detailed Study by Proton Nuclear Magnetic Resonance of Walnut Oil Oxidation - Sofía del Caño-Ochoa; Ainhoa Ruiz-Aracama; María D. Guillén (MDPI AG, 2022)
Lipid oxidation causes food degradation and the formation of toxic compounds. Therefore, the addition to foods of compounds able to avoid, delay or minimize this degradative process is a commonly used strategy. Nevertheless, neither the identity of most of the formed compounds in this complex process nor the way in which their formation is affected by the strategy used are well known. In this context, the effect the temperature increase and the enrichment level in alpha-tocopherol on the evolution of the walnut oil oxidation, as a model of an oil rich in polyunsaturated omega-6 acyl groups, submitted to storage conditions, are tackled by 1H NMR. The study has allowed knowing the degradation kinetic of both the oil acyl groups and alpha-tocopherol, the identification of a very high number of oxylipins and the kinetic of their formation. The temperature increase accelerates the formation of all oxylipins, favouring the formation of hydroperoxy conjugated E,E-dienes and related derivatives versus that of the Z,E-isomers. The enrichment in alpha-tocopherol accelerates the formation of hydroperoxy conjugated Z,E-dienes and related derivatives, and delays in relation to the formation of the former that of the E,E-isomers and related derivatives, hindering, to a certain extent, the formation of the latter in line with the enrichment level.